LAIT: a local ancestry inference toolkit - Daniel Hui; Zhou Fang; Jerome Lin; Qing Duan; Yun Li; Ming Hu; Wei Chen (BMC Genetics, 2017)
Abstract Background Inferring local ancestry in individuals of mixed ancestry has many applications, most notably in identifying disease-susceptible loci that vary among different ethnic groups. Many software packages are available for inferring local ancestry in admixed individuals. However, most of these existing software packages require specific formatted input files and generate output files in various types, yielding practical inconvenience. Results We developed a tool set, Local Ancestry Inference Toolkit (LAIT), which can convert standardized files into software-specific input file formats as well as standardize and summarize inference results for four popular local ancestry inference software: HAPMIX, LAMP, LAMP-LD, and ELAI. We tested LAIT using both simulated and real data sets and demonstrated that LAIT provides convenience to run multiple local ancestry inference software. In addition, we evaluated the performance of local ancestry software among different supported software packages, mainly focusing on inference accuracy and computational resources used. Conclusion We provided a toolkit to facilitate the use of local ancestry inference software, especially for users with limited bioinformatics background.